Discriminative touch and emotional touch. - McGlone, F; Vallbo, AB; Olausson, H; Loken, L; Wessberg, J (2007)
Somatic sensation comprises four main modalities, each relaying tactile, thermal, painful, or pruritic (itch) information to the central nervous system. These input channels can be further classified as subserving a sensory function of spatial and temporal localization, discrimination, and provision of essential information for controlling and guiding exploratory tactile behaviours, and an affective function that is widely recognized as providing the afferent neural input driving the subjective experience of pain, but not so widely recognized as also providing the subjective experience of affiliative or emotional somatic pleasure of touch. The discriminative properties of tactile sensation are mediated by a class of fast-conducting myelinated peripheral nerve fibres--A-beta fibres--whereas the rewarding, emotional properties of touch are hypothesized to be mediated by a class of unmyelinated peripheral nerve fibres--CT afferents (C tactile)--that have biophysical, electrophysiological, neurobiological, and anatomical properties that drive the temporally delayed emotional somatic system. CT afferents have not been found in the glabrous skin of the hand in spite of numerous electrophysiological explorations of this area. Hence, it seems reasonable to conclude that they are lacking in the glabrous skin. A full understanding of the behavioural and affective consequences of the differential innervation of CT afferents awaits a fuller understanding of their function.